A Pilot Study Evaluating the Prevalence of Cervical Spine Dysfunction Among Students of Dentistry at the Medical University - Kuć, Joanna; Żendzian-Piotrowska, Małgorzata (Frontiers in Neurology, 2020)
Introduction Cervical pain affects most people at some stage, especially middle-aged. It is one of the symptoms of cervical spine dysfunction. The prevalence of neck pain varies and depends on the population studied. The aim of the study was to assess the prevalence of cervical spine dysfunction among dentistry students from a medical university. Material and methods The study was conducted on a group of 112 randomly chosen, generally healthy students (73 women and 39 men) of the faculty of medicine, division of dentistry at a medical university, aged 20–32, average 22.88 ± 2.7. The survey was based on a questionnaire about possible symptoms and disorders of the cervical spine in the 6 preceeding months. A bodychart was used to visualize ailments in relation to the scheme of human body, and a Graded Chronic Pain Scale was applied to assess levels of pain. Additionally, the Perceived Stress Scale and Neck Disability Index were evaluated. Results With respect to the questionnaire about possible symptoms of cervical spine disorders in the 6 preceeding months, 22.32% of students declared headaches 2–3 times a week, and 45.53% 2–3 times a month. 42.85% of the participants reported difficulties with concentration, 56.25% showed attention issues, and 25% had problems with memory. Moreover, 9.82% of the subjects suffered from depression, and 27.67% declared mood disorders. The bodychart revealed the occurrence of pain within the cervical spine in 47.32% of the respondents. 31.25% of students declared discomfort in the suboccipital area. In 57.14% of people, low intensity of chronic pain without functional disorders was noted. A moderate level of stress was reported in 58.03% of students. Mild cervical spine disorders were found in 53.57% of cases. Conclusion The relatively high prevalence of symptoms of the cervical spine dysfunction, chronic pain, stress and neck disability among young people may indicate that numerous spinal disorders identified in dentists result not only from their profession, in which spine is significantly overloaded, but also individual predispositions including biopsychosocial profile and the changing lifestyle habits of young people.